2001
DOI: 10.1073/pnas.051042298
|View full text |Cite
|
Sign up to set email alerts
|

A phosphatidylinositol 3-kinase/Akt/mTOR pathway mediates and PTEN antagonizes tumor necrosis factor inhibition of insulin signaling through insulin receptor substrate-1

Abstract: Tyrosine phosphorylation of insulin receptor substrate-1 (IRS-1) by the insulin receptor permits this docking protein to interact with signaling proteins that promote insulin action. Serine phosphorylation uncouples IRS-1 from the insulin receptor, thereby inhibiting its tyrosine phosphorylation and insulin signaling. For this reason, there is great interest in identifying serine͞threonine kinases for which IRS-1 is a substrate. Tumor necrosis factor (TNF) inhibited insulin-promoted tyrosine phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
274
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(291 citation statements)
references
References 62 publications
14
274
1
2
Order By: Relevance
“…In this work we detected for the first time a significant enlargement of Ptpn1 mRNA and protein expression in brown adipocytes treated with TNFα, as well as an increase in phosphatase activity. Numerous sources of evidence suggest that phosphatases are used by TNFα to block insulin signalling at different levels [38][39][40]. Moreover, studies with obese rats have shown that expression of leucocyte common antigen-related protein tyrosine phosphatase in liver is downregulated after TNFα blockade [41], and in rat hepatoma cells TNFα increased SHIP2 production.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we detected for the first time a significant enlargement of Ptpn1 mRNA and protein expression in brown adipocytes treated with TNFα, as well as an increase in phosphatase activity. Numerous sources of evidence suggest that phosphatases are used by TNFα to block insulin signalling at different levels [38][39][40]. Moreover, studies with obese rats have shown that expression of leucocyte common antigen-related protein tyrosine phosphatase in liver is downregulated after TNFα blockade [41], and in rat hepatoma cells TNFα increased SHIP2 production.…”
Section: Discussionmentioning
confidence: 99%
“…TNFa binds to its receptor and activates downstream inflammatory signaling pathways including IKK, mTORC or JNK. In turn, these effectors recruit downstream molecules, respectively nuclear factor-kappa B (NFkB), S6 kinase (S6K) and activator protein-1 (AP-1), which inhibit IRS phosphorylation, subsequently impairing insulin signaling in the liver (Kamada et al, 2008;Lumeng et al, 2008;Ozes et al, 2001) (Fig. 2).…”
Section: Ectopic Fat Accumulation Promotes Hepatic Insulin Resistancementioning
confidence: 99%
“…32,33 Therefore, to further investigate the mechanisms were subjected to immunoblot analysis with anti-SOCS-7 and anti-␤-actin antibodies (C). We quantified the signal of SOCS-7 by densitometry and normalized it using ␤-actin signal as reference protein.…”
Section: Effect Of Hcv Core Protein On Mtor Activitymentioning
confidence: 99%